The influence of the breathing action on net drag force production in front crawl swimming - Formosa, D.; Sayers, M. G. L.; Burkett, B. (International Journal of Sports Medicine, 2014)
20 elite swimmers completed a total of 6 randomized net drag force trials in 2 conditions (i) 3 breathing and (ii) 3 non-breathing. Net drag force was measured using an assisted motorized dynamometer device mounted upon a Kistler force-platform. The male participants demonstrated no statistical differences in stroke rates between breathing and non-breathing trials. Female participants, however, demonstrated a statistical difference stroke rate. The male participants demonstrated that the breathing action caused a greater (26%) net drag force compared to the females (16%). To further understand the influence of breathing on swimming technique, each stroke was analyzed and comparisons were made between the breathing and non-breathing conditions. The male participants demonstrated a similar minimum net drag force when comparing the breathing and non-breathing conditions. Analysis showed that minimum net drag force and maximum net drag force for the males changed when integrating the breathing action, while female participants demonstrated similar swimming technique, regardless of condition or stroke.